Spectroelectrochemistry of phthalocyanines - (:unkn) unknown (Springer International Publishing, 2016)
Conventional electroanalytical methods: voltammetry, amperometry, and so on are excellent methods to determine concentrations, to drive thermodynamic parameters of a system (peak potential, free energy change, entropy, etc.), and to clarify redox reaction mechanisms. However, these techniques are not themselves enough to identify unknown intermediates and products formed during a redox reaction. A combinatory technique, spectroelectrochemistry (SEC) can solve this problem. Since SEC allows for a more complete analysis of electron transfer reactions and complex redox processes. Although SEC techniques have been well developed during the last few decades, their applications in different fields have recently become more widespread (Gale in Spectroelectrochemistry: theory and practice. Springer, New York, 1988 [1]). This chapter is meant to serve a guide where SEC can clarify the understanding of the redox reactions through identifications of the intermediates and products of various phthalocyanines. Phthalocyanines (Pcs) are one of the most prominent ligand types in coordination chemistry. They are used as dyes, photosensitizers, catalysts, sensors, and electrochromic materials, which are well generally related with their versatile redox properties and their outstanding roles in these areas are well documented (Sorokin in Chem Rev 113(10):8152-8191, 2013; Kobayashi and Konami in Phthalocyanines: properties and applications. VCH, New York, 1996; Milaeva et al. in the phthalocyanines, properties and applications. Wiley, New York, pp. 162-227, 1992 [2-4]). One of the most distinctive properties of Pcs is the rich redox behaviors, up to four reductions and two oxidation reactions. On the other hand many of the metal ions in the core of Pcs [in metallophthalocyanines (MPcs)] and some substituents can give extra redox reactions between the electron transfer reactions of Pc ring. A clear assignment of such redox reactions in MPcs is not easy to make with only voltammetric analyses. For a profound understanding of the electrochemical behaviors of MPcs, e.g., interaction of Pc ring and metal centers or axial, peripheral, and/or nonperipheral substituents, electrochemical and spectroscopic and of course SEC experiments are in general carried out (Ou et al. in Macroheterocycles 4(3):164-170, 2011; Alemdar et al. in Polyhedron 28(17):3788-3796, 2009; Sekota and Nyokong in Polyhedron 15(17):2901-2908, 1996; Arici et al. in Electrochim Acta 87:554-566, 2013; Burat et al. in Electroanal 24(2):338-348, 2012; Simicglavaski et al. in J Electrochem Soc 134(3):C130, 1987 [5-10]). This chapter will report on how SEC can contribute to the assignments of different classes of MPc complexes. Since there has been extensive investigation on the electrochemical properties of MPcs, this chapter focuses on the generalization of SEC responses of the similar types of the complexes. We classified MPcs as metal-free phthalocyanines (H2Pcs), metallophthalocyanines bearing redox inactive metal centers (MPcs-RIAM), metallophthalocyanines bearing redox active metal centers (MPcs-RAM), metallophthalocyanines carrying redox active substituents (MPcs-RAS), and sandwich metallophthalocyanines (MPc2s) due to the characteristic SEC response differences between these groups of complexes. © Springer International Publishing Switzerland 2016.
Keywords: Electrochemistry and spectroelectrochemistry of CoPcs; Electrochemistry and spectroelectrochemistry of FePcs; Electrochemistry and spectroelectrochemistry of TiOPcs; Electrochemistry and spectroelectrochemistry of X-Mn(III)Pcs; Metal-free phthalocyanines; Metallophthalocyanines (MPcs-RAM) bearing redox active metal centers; Metallophthalocyanines (MPcs-RIAM) bearing redox Inactive metal centers; Phthalocyanines; Sandwich metallophthalocyanines (MPc2); Spectroelectrochemistry; Spectroelectrochemistry of phthalocyanines